2010
DOI: 10.1073/pnas.0907801107
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of 83 plastid genes further resolves the early diversification of eudicots

Abstract: Although Pentapetalae (comprising all core eudicots except Gunnerales) include ≈70% of all angiosperms, the origin of and relationships among the major lineages of this clade have remained largely unresolved. Phylogenetic analyses of 83 protein-coding and rRNA genes from the plastid genome for 86 species of seed plants, including new sequences from 25 eudicots, indicate that soon after its origin, Pentapetalae diverged into three clades: (i) a "superrosid" clade consisting of Rosidae, Vitaceae, and Saxifragale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
644
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 630 publications
(703 citation statements)
references
References 51 publications
(64 reference statements)
43
644
2
3
Order By: Relevance
“…However, Boraginales have been variously resolved as sister to Lamiales (Soltis & al., 2011;Refulio-Rodríguez & Olmstead, 2014), Solanales (Weigend & al., 2014), Gentianales (Stull & al., 2015), or Solanales + Gentianales (Moore & al., 2010), always with low to moderate support only.…”
Section: Introductionmentioning
confidence: 99%
“…However, Boraginales have been variously resolved as sister to Lamiales (Soltis & al., 2011;Refulio-Rodríguez & Olmstead, 2014), Solanales (Weigend & al., 2014), Gentianales (Stull & al., 2015), or Solanales + Gentianales (Moore & al., 2010), always with low to moderate support only.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis thaliana and petunia belong to the rosids and asteroids, respectively, which are thought to have diverged ;100 million years ago (Moore et al, 2010); therefore, comparison of the molecular mechanisms controlling their flower development helps to estimate the antiquity and divergence of this floral network. Previous work has shown that despite similarities in the architecture of petunia and Arabidopsis flowers, the molecular mechanisms that underlie organ identity specification in both species are not necessarily identical.…”
Section: Introductionmentioning
confidence: 99%
“…6a). Previous studies left the phylogeny of rosids, asterids and Caryophyllales unresolved 10 or classified Caryophyllales as a subclade of asterids 11 . A species tree inferred from the collection of gene trees strongly suggested that Beta vulgaris branched off before the separation of asterids and rosids (Fig.…”
mentioning
confidence: 99%